The role of antibody polyspecificity and lipid reactivity in binding of broadly neutralizing anti-HIV-1 envelope human monoclonal antibodies 2F5 and 4E10 to glycoprotein 41 membrane proximal envelope epitopes - Alam, S Munir; McAdams, Mildred; Boren, David; Rak, Michael; Scearce, Richard M; Gao, Feng; Camacho, Zenaido T; Gewirth, Daniel; Kelsoe, Garnett; Chen, Pojen; Haynes, Barton F (Journal of Immunology, 2007)
Two neutralizing human mAbs, 2F5 and 4E10, that react with the HIV-1 envelope gp41 membrane proximal region are also polyspecific autoantibodies that bind to anionic phospholipids. To determine the autoantibody nature of these Abs, we have compared their reactivities with human anti-cardiolipin mAbs derived from a primary antiphospholipid syndrome patient. To define the role of lipid polyreactivity in binding of 2F5 and 4E10 mAbs to HIV-1 envelope membrane proximal epitopes, we determined the kinetics of binding of mAbs 2F5 and 4E10 to their nominal gp41 epitopes vs liposome-gp41 peptide conjugates. Both anti-HIV-1 mAbs 2F5 and 4E10 bound to cardiolipin with K(d) values similar to those of autoimmune anti-cardiolipin Abs, IS4 and IS6. Binding kinetics studies revealed that mAb 2F5 and 4E10 binding to their respective gp41 peptide-lipid conjugates could best be defined by a two-step (encounter-docking) conformational change model. In contrast, binding of 2F5 and 4E10 mAbs to linear peptide epitopes followed a simple Langmuir model. A mouse mAb, 13H11, that cross-blocks mAb 2F5 binding to the gp41 epitope did not cross-react with lipids nor did it neutralize HIV-1 viruses. Taken together, these data demonstrate the similarity of 2F5 and 4E10 mAbs to known anti-cardiolipin Abs and support the model that mAb 2F5 and 4E10 binding to HIV-1 involves both viral lipid membrane and gp41 membrane proximal epitopes.